Aptamer-conjugated graphene oxide-based surface assisted laser desorption ionization mass spectrometry for selective extraction and detection of Aβ1–42 in an Alzheimer’s disease SH-SY5 cell model - Song, Gongshuai; Shui, Ruofan; Wang, Danli; Fang, Ruosi; Yuan, Tinglan; Li, Ling; Feng, Junli; Gao, Feng; Shen, Qing; Gong, Jinyan; Zheng, Fuping; Zhang, Manman (Frontiers in Aging Neuroscience, 2022)
The generation and accumulation of amyloid-beta peptide (Aβ1-42) in amyloid plaques are key characteristics of Alzheimer's disease (AD), thus specific detection of Aβ1-42 is essential for the diagnosis and treatment of AD. Herein, an aptamer-conjugated graphene oxide (Apt-GO) sensor was synthesized by π-π and hydrophobic interactions using thiol poly (ethylene glycol) amine (SH-PEG-NH2) as a spacer unit. Then, it was applied to selective capture Aβ1-42, and the resulting complex was directly analyzed by surface-assisted laser desorption ionization mass spectrometry (SALDI-MS). The results revealed that the Apt-GO could enhance the detection specificity and reduce non-specific adsorption. This method was validated to be sensitive in detecting Aβ1-42 at low level in human serum (ca. 0.1 μM) within a linear range from 0.1 to 10 μM. The immobilizing amount of aptamer on the GO was calculated to be 36.1 nmol/mg (RSD = 11.5%). In conclusion, this Apt-GO based SALDI-MS method was sensitive and efficient in selective extraction and detection of Aβ1-42, which proved to be a good option for early AD diagnosis.